Soil Properties and Bacterial Communities Associated with the Rhizosphere of the Common Bean after Using Brachiaria brizantha as a Service Crop: A 10-Year Field Experiment - Aban, Carla Luciana (2023)
Intensive agricultural farming practices, such as monoculture, require long bare fallow periods and the overuse of agrochemicals, which compromise soil health over time. Increasing plant diversity in agroecosystems with service crops represents a promising alternative to achieving sustainability goals. However, how specific cover crop species influence the abundance and structure of soil bacterial communities remains to be solved. In this study, we assessed the effects of B. brizantha in two different agricultural cycles for 10 years in a common bean monoculture system in the northwestern region of Argentina (NWA) by measuring chemical, physical, and microbiological parameters in the rhizosphere, as well as by screening the rhizobiome using 16S rRNA sequencing. The ten-year inclusion of B. brizantha had a positive impact on properties in the rhizosphere compared to the common bean monoculture. The bacterial beta-diversity was different among treatments, but not the alpha-diversity. The most abundant phyla were Actinobacteria, Proteobacteria, Acidobacteria, Chloroflexi and Myxococcota. The predicted functions related to chemoheterotrophy and aerobic chemoheterotrophy were increased under B. brizantha treatments compared to the bean monoculture. The inclusion of the pasture B. brizantha contributed to restoring soil health and minimizing soil degradation.